Kapalı Redüksiyon ve K-Teli İle Tedavi Edilen Radius Alt Uç Kırıklarında Dorsal Korteks Parçalanmasının Radyografik Sonuçlara Etkisi - Vatansever, Aziz; Pişkin, Ahmet; Kayalar, Murat; Bal, Emin; Ada, Sait (My University, 2007)
Amaç: Bu çalışmada, kapalı redüksiyon ve K-teli tespiti uygulanan instabil radius alt uç kırıklarında eşlik edebilecek dorsal korteks parçalanmasının radyografik sonuçlara etkisi değerlendirildi. Çalışma planı: Radius alt uç kırığı nedeniyle kapalı redüksiyon ve K-teli ile tespit uygulanan 42 hasta değerlendirildi. Kırıkların tümü eklem dışı, dorsale açılanma gösteren instabil kırıklardı. Hastalar radius alt uç metafizinde dorsal yüzde parçalanma ve buna bağlı yan grafide görülen radyoopasite olup olmamasına göre iki gruba ayrıldı. Otuz hastada (13 erkek, 17 kadın; ort. yaş 56; dağılım 22-77) dorsal kortekste parçalanma görülmedi. Bu grupta takip süresi ortalama 8.8 aydı (dağılım 3-106 ay). On iki hastada (8 erkek, 4 kadın; ort. yaş 48; dağılım 18-76) dorsal kortekste parçalanma izlendi. Bu grupta ortalama takip süresi 5.5 aydı (dağılım 3-131 ay). Kırık sonrası ve kaynama sonrası çekilen yan grafilerde palmar eğim açısı, arka-ön grafilerde radial eğim açısı ve radial uzunluk ölçüldü; sonuçlar iki grup arasında karşılaştırıldı. Sonuçlar: Her iki grupta da radial eğim açısı, palmar eğim açısı ve radial uzunluk ameliyat sonrasında anlamlı düzelme gösterdi (p0.05). Hiçbir hastada önemli bir komplikasyona rastlanmadı. Çıkarımlar: Dorsal metafizer kortikal parçalanma radyografik sonuçları etkilememektedir. Kapalı redüksiyon ve K-teli ile tespit, dorsal korteks parçalanmasının eşlik ettiği kırıklarda dahi güvenli ve etkin bir tedavi yöntemidir.

Objectives: The purpose of this study was to evaluate the effect of dorsal cortical comminution on radiographic outcome of unstable distal radius fractures after treatment with closed reduction and K-wire fixation. Methods: Forty-two patients were treated with closed reduction and K-wire fixation for unstable, extra-articular distal radius fractures with dorsal angulation. The patients were evaluated in two groups depending on the presence or absence of dorsal metaphyseal cortical comminution observed as a radiopacity on lateral radiographs. Thus, 30 patients (13 males, 17 females; mean age 56 years; range 22 to 77 years) did not have dorsal cortical comminution, whereas 12 patients (8 males, 4 females; mean age 48 years; range 18 to 76 years) did. The mean follow-up period was 8.8 months (range 3 to 106 months) in the former, and 5.5 months (range 3 to 131 months) in the latter groups. Radiographic parameters were compared including palmar tilt measured on lateral, radial inclination and radial length on posteroanterior radiographs obtained before treatment and after union. Results: Radial inclination, palmar tilt, and radial length showed significant improvements in both groups (p<0.05). The results were acceptable in all the patients with achievement of standard reference values. The presence of dorsal cortical comminution did not have any significant effect on radiographic parameters (p>0.05). No significant complications were encountered during the follow-up period. Conclusion: Dorsal cortical metaphyseal comminution does not have an adverse effect on radiographic results. Treatment with closed reduction and K-wire fixation is safe and effective even in the presence of dorsal cortical comminution. Key words: Bone wires; fracture fixation/methods; radius fractures/ surgery/radiography; wrist injuries/surgery.
The effect of dorsal cortical comminution on radiographic results of unstable distal radius fractures treated with closed reduction and K-wire fixation
Keywords: Cerrahi